Resiliensi Sekolah Misi YATAPS Pasca Pandemi Covid-19: Penyesuaian, Tantangan, dan Peluang - Keun, Song Young; Hijjang, Pawennari; Poli, Agustina Ivonne; Numberi , Gerdha K.I. (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2025)
This research examines the resilience of informal education at YATAPS Mission School in Papua after the Covid-19 pandemic. With the pandemic drastically changing the education landscape, informal education is seen as an effective alternative to formal learning. The study aims to understand how informal education adapts and functions in the post-pandemic situation and its impact on student learning. The research utilized anthropological qualitative methods, including interviews, observation, and document analysis. Students, teachers, and parents were purposively selected to gain diverse perspectives. The results indicate that informal education at YATAPS Mission School has successfully adapted to the post-Covid-19 situation, with various learning activities happening outside the classroom using local resources and community strengths. The findings highlight the role of informal education in complementing formal education, building character, strengthening social ties, and increasing parental involvement. Despite challenges like limited technology access, the school community found innovative solutions to ensure education continuity. This research is expected to inform education policy in Papua and guide future research on informal education.